PENGENDALIAN KOROSI PADA SISTEM PENDINGIN MENGGUNAKAN PENAMBAHAN ZAT INHIBITOR - Atmadja, Sugeng Tirta (ROTASI, 2010)
Corrosion is defined as the destruction or deterioration of a material because of reaction with its environtment. Corrosion can attack all kinds metals. Corrosion can occur at cooling system which always contact with water. It is caused by chemical reaction between metal surface and water. This corrosion can be controlled by adding inhibitor substance into cooling system. Inhibitor is a substance that when added in smalled concentration to an environtment decrease the corrosion rate. With adding inhibitor properly into cooling system, agresivity of corrosion attack will be reduced. Therefore we keep performance of cooling system.